Romance languages and linguistic theory 13 selected papers from "Going Romance" 29, Nijmegen - Berns, Janine; Jacobs, Haike, 1961-; Nouveau, Dominique (Romance languages and linguistic theory (RLLT),, 2018)
"In the three decades of its existence, the annual Going Romance conference has turned out to be the major European discussion forum for theoretically relevant research on Romance languages where current theoretical ideas about language in general and about Romance languages in particular are exchanged. The twenty-ninth Going Romance conference was organized by the Radboud University and took place in December 2015 in Nijmegen. The present volume contains a selection of 19 peer-reviewed articles dealing with syntax, phonology, morphology, semantics and acquisition of the Romance languages. They represent the wide range of topics at the conference and the variety of research carried out on Romance languages within theoretical linguistics and will be of interest to scholars in Romance and in general linguistics"--